2020
DOI: 10.1007/s40866-020-00080-w
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Domain Feature Extraction for Improved Clustering of Smart Meter Data

Abstract: The advent of smart grid is a revolution that has enabled power distribution in a more efficient way. However, load forecasting, demand response management and accurate consumer load profiling using smart meter data continue to be challenging industry and research problems. Clustering is an efficient technique for load profiling. K-means clustering algorithm for clustering electricity consumers based on raw meter data directly result in cumbersome, redundant and inefficient computations. This paper presents a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The deficiency of energy sources in BANs can also be improved by integrating energy harvesting solutions, that transform body scale clean energies into electrical energy [31,32], to supply node batteries.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…The deficiency of energy sources in BANs can also be improved by integrating energy harvesting solutions, that transform body scale clean energies into electrical energy [31,32], to supply node batteries.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…More specifically, SC indicates whether the data samples were correctly clustered and separated (clusters coherence and goodness). The SC for data (i) is computed as [20]:…”
Section: Discussionmentioning
confidence: 99%
“…Clustering analysis and technology network analysis were used to identify topics in nuclear waste management over time. Shamim and Rihan ( 2020 ) compared using k-means clustering and k-means clustering with feature extraction in smart metering electricity. Results of their experiments showed that clustering using features from raw data obtained better performance than direct raw data.…”
Section: Applications Of Clusteringmentioning
confidence: 99%